2005
DOI: 10.1353/asi.2005.0007
|View full text |Cite
|
Sign up to set email alerts
|

Past Human Activity and Geomorphological Change in a Guano-Rich Tropical Cave Mouth: Initial Interpretations of the Late Quaternary Succession in the Great Cave of Niah, Sarawak

Abstract: This paper presents initial interpretations of the processes and events responsible for the late Quaternary sequence in the West Mouth of the Great Cave of Niah, in the hot and humid lowland rainforest and swamp forest of Sarawak in Malaysian Borneo. It evaluates the geomorphological context of the site within the known pattern of rapid late Quaternary climate change. Attention is given to the proximity to the sea and the likelihood of humid tropical or cooler drier conditions. The stratigraphic succession is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 39 publications
5
39
0
Order By: Relevance
“…This is consistent with the model, asserted in the literature (e.g. Gilbertson et al, 2005), that prior to the LGM the coastal margins of northern Borneo were probably some considerable distance away, and moderate to fastflowing streams predominated. Although there was limited continued exploitation of chelonian species from streams during the post-LGM period, the focus of foraging attention -along with the kinds of habitats accessible -had by this This research demonstrates how the detailed study of chelonian remains can provide important archaeozoological information on human resource procurement and palaeoecological reconstruction, and combined with the analysis of other classes of vertebrates (and invertebrates), can aid in the development of a robust framework developing an understanding of past human behaviours.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with the model, asserted in the literature (e.g. Gilbertson et al, 2005), that prior to the LGM the coastal margins of northern Borneo were probably some considerable distance away, and moderate to fastflowing streams predominated. Although there was limited continued exploitation of chelonian species from streams during the post-LGM period, the focus of foraging attention -along with the kinds of habitats accessible -had by this This research demonstrates how the detailed study of chelonian remains can provide important archaeozoological information on human resource procurement and palaeoecological reconstruction, and combined with the analysis of other classes of vertebrates (and invertebrates), can aid in the development of a robust framework developing an understanding of past human behaviours.…”
Section: Resultssupporting
confidence: 93%
“…70%) of our sample is associated with what we have defined as 'Phase II' activity (Piper et al, 2008;Piper & Rabett, 2009;Rabett et al, 2006, in prep.). By counting all recovered fragments per given spit (including unidentifiable fragments), we determined a spatial profile that indicated that the Phase II bone assemblage had probably accumulated within a shallow depression related to the sinkhole feature predicted to underlie the deposits here (Gilbertson et al, 2005). At its deepest point, near the centre of the space under the rock shelter, this assemblage reaches around 60 inches (152.4 cm) and slopes upwards to the northwest and southeast to a depth of 30 inches (76.2 cm).…”
Section: Pelochelys Cantoriimentioning
confidence: 99%
“…The human fossils found in Tabon and Callao Caves are very significant discoveries since they are the oldest human remains known so far from the Philippines and from Island Southeast Asia as a whole, together with the fossils from Niah Cave in Sarawak, Borneo Island (Harrisson 1959;Barker 2005;Gilbertson et al 2005;Barker et al 2007). The earliest securely dated archaeological evidence indicates a human presence in Australia at around 40-45 kya (O'Connell and Allen 2004), but very few Australian fossils of this antiquity were known until now (Thorne et al 1999;Brown 2000;Gillespie and Roberts 2000;Bowler et al 2003).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The earliest datable specimens are a fragmentary left magnum from trench HQ/5 at 84-87 inches below the 1950s ground surface, and a subterminal phalanx of the first right or fourth left digit of the forefoot from trench HQ/9(B) at depth 78-81 inches (Hooijer, 1963; Table 1, N1 and N12). As part of the NCP re-evaluation of the site, temporal and spatial patterning of the vertebrate remains (Rabett et al, 2006) and geomorphic modelling of the processes of deposit formation (Gilbertson et al, 2005) have determined that artefacts from the HQ series of trenches at equivalent depths as the tapir bones date to 35,000-40,000 years ago. The distal head of a lateral metapodial, provisionally a right 2 nd metatarsal, from trench Y/1(A) at depth 54-60 inches (Table 1, N6), is probably within the same range of dates.…”
Section: Palaeozoological Evidencementioning
confidence: 99%